2000
DOI: 10.1128/jvi.74.23.11008-11016.2000
|View full text |Cite
|
Sign up to set email alerts
|

The N-Terminal V3 Loop Glycan Modulates the Interaction of Clade A and B Human Immunodeficiency Virus Type 1 Envelopes with CD4 and Chemokine Receptors

Abstract: We investigated the underlying mechanism by which the highly conserved N-terminal V3 loop glycan of gp120 conferred resistance to neutralization of human immunodeficiency virus type 1 (HIV-1). We find that the presence or absence of this V3 glycan on clade A and B viruses accorded various degrees of susceptibility to neutralization by antibodies to the CD4 binding site, CD4-induced epitopes, and chemokine receptors. Our data suggest that this carbohydrate moiety on gp120 blocks access to the binding site for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
1
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 49 publications
7
70
1
2
Order By: Relevance
“…Changes common to both clones included the loss of a potential N-linked glycosylation site in the V1 variable loop, the repositioning of such a site in the V2 loop, and the gain of a third glycosylation site at the base of the V3 loop. We have previously shown that the potential glycosylation changes in V1 and V3 contributed to the neutralization-resistant phenotype of SHIV SF33A (4,38). Of note, the set of 22 mutations common to clones SHIV SF33A2 and SHIV SF33A5 were also present in env genes amplified directly from Mmu 25814, the animal from which the SHIV SF33A isolate was originally recovered (36).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes common to both clones included the loss of a potential N-linked glycosylation site in the V1 variable loop, the repositioning of such a site in the V2 loop, and the gain of a third glycosylation site at the base of the V3 loop. We have previously shown that the potential glycosylation changes in V1 and V3 contributed to the neutralization-resistant phenotype of SHIV SF33A (4,38). Of note, the set of 22 mutations common to clones SHIV SF33A2 and SHIV SF33A5 were also present in env genes amplified directly from Mmu 25814, the animal from which the SHIV SF33A isolate was originally recovered (36).…”
Section: Resultsmentioning
confidence: 99%
“…The immunoprecipitates were washed four times in 1 ml of KEB and resuspended in sodium dodecyl sulfate loading buffer for analysis by immunoblotting. Samples were run on a 4 to 12% polyacrylamide gradient gel (Novex, San Diego, Calif.) and immunoblotted with goat anti-gp120 serum Env2-3 (Chiron) as previously described (38). The total envelope glycoprotein content of transfected cells was assessed by direct lysis of 293T cells in 100 l of KEB followed by protein extraction, incubation of the extracts with 5 l of preadsorbed pooled HIV sera for 2 h at 4°C, addition of 50 l of protein G-Sepharose, and overnight incubation at 4°C.…”
Section: Cellsmentioning
confidence: 99%
“…Malenbaum and colleagues have demonstrated that the removal of glycosylation at position 301 resulted in an increased neutralizing sensitivity of HIV-1 to CD4 BS antibodies. 187 Furthermore, mutant virus lacking 301 glycan also demonstrated sensitivity to CD4i antibodies. In another study, elimination of N-linked glycosylation in the V1 and V2 loops of pathogenic SIV mac239 rendered the virus more sensitive www.landesbioscience.com…”
Section: Structural Optimization To Target Conserved Neutralization Ementioning
confidence: 99%
“…1A). Eliminating the glycan from residue 301 at the base of V3 via mutagenesis (77)(78)(79), or generating smaller glycans by producing gp120 in GnT Ϫ/Ϫ cells (14), increases the accessibility of V3 neutralization epitopes to antibodies. Consistent with these observations, mAb 447-52D and 19b both bound more strongly to deglycosylated trimers than untreated ones (Fig.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%